Realization of Free-Space Long-Distance Self-Healing Bessel Beams - Vetter, Christian; Steinkopf, Ralf; Bergner, Klaus; Ornigotti, Marco; Nolte, Stefan; Gross, Herbert; Szameit, Alexander (Laser & Photonics Reviews, 2019)
A new approach for generating long-distance self-healing Bessel beams, which is based on a ring-shaped (annular) lens and a spherical lens in 4f-configuration, is reported. With this, diffraction-free light evolution of a zeroth order Bessel beam over several meters is shown and available scaling opportunities that surpass current technologies by far are discussed. Furthermore, it is demonstrated how this setup can be adapted to create Bessel beam superpositions, realizing the longest ever reported optical conveyor beam and helicon beam, respectively. Last, the self-healing capabilities of the beams are tested against strong opaque and non-opaque scatterers, which again emphasizes the great potential of this new method.
CRIS-Team Scopus Importer:2023-04-20
Keywords: beam-shaping; Bessel-beams; laser-technology; self-healing; telecommunication